Akkermansia Muciniphila Protects Against Atherosclerosis by Preventing Metabolic Endotoxemia-Induced Inflammation in Apoe−/− Mice. Issue 24 (14th June 2016) - Li, Jin; Lin, Shaoqiang; Vanhoutte, Paul M.; Woo, Connie W.; Xu, Aimin
Abstract : Background—: Altered composition of the gut microbiota is involved in both the onset and progression of obesity and diabetes mellitus. However, the link between gut microbiota and obesity-related cardiovascular complications has not been explored. The present study was designed to investigate the role of Akkermansia muciniphila, a mucin-degrading bacterium with beneficial effects on metabolism, in the pathogenesis of atherosclerosis in apolipoprotein E–deficient ( Apoe −/− ) mice. Methods and Results—: Apoe −/− mice on normal chow diet or a Western diet were treated with A muciniphila by daily oral gavage for 8 weeks, followed by histological evaluations of atherosclerotic lesion in aorta. Real-time polymerase chain reaction analysis demonstrated that the fecal abundance of A muciniphila was significantly reduced by Western diet. Replenishment with A muciniphila reversed Western diet–induced exacerbation of atherosclerotic lesion formation without affecting hypercholesterolemia. A muciniphila prevented Western diet–induced inflammation in both the circulation and local atherosclerotic lesion, as evidenced by reduced macrophage infiltration and expression of proinflammatory cytokines and chemokines. These changes were accompanied by a marked attenuation in metabolic endotoxemia. A muciniphila –mediated reduction in circulating endotoxin level could be attributed to the induction of intestinal expression of the tight junction proteins (zona occuldens protein-1 and occludin), thereby reversing Western diet–induced increases in gut permeability. Long-term infusion of endotoxin to Apoe −/− mice reversed the protective effect of A muciniphila against atherosclerosis. Conclusion—: A muciniphila attenuates atherosclerotic lesions by ameliorating metabolic endotoxemia-induced inflammation through restoration of the gut barrier. Abstract : Supplemental Digital Content is available in the text.